HIDD’n HADD in Intelligent Design - Atkinson, Andrew Ross (Journal of cognition and culture, 2020)
The idea that religious belief is ‘almost inevitable’ is so forcefully argued by Justin Barrett (2004, 2012) that it can warrant justifiable concern (Shook, 2017; Sterelny, 2018) - especially since he claims atheism is an unnatural handicap (2012, p. 203). In this article, I argue that religious belief in Homo sapiens isn’t inevitable - and that Barrett does agree when pushed. I describe the role played by a Hyperactive Agency Detection Device (HADD) in the generation of belief in God as necessary but insufficient in explaining religious culture - I distance myself from some common conceptions of HADD and the view I take of it is unorthodox. I point out that the conclusion to Barrett’s (2004) book, ‘Why Would Anyone Believe in God?’ is a fine example of the very hyperactive agency detection Barrett himself describes, and is therefore highly suspect.